2021
DOI: 10.7554/elife.68039
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor impairments and therapeutic implications revealed by a mutation associated with infantile Parkinsonism-Dystonia

Abstract: Parkinson disease (PD) is a progressive, neurodegenerative disorder affecting over 6.1 million people worldwide. Although the cause of PD remains unclear, studies of highly penetrant mutations identified in early-onset familial parkinsonism have contributed to our understanding of the molecular mechanisms underlying disease pathology. Dopamine (DA) transporter (DAT) deficiency syndrome (DTDS) is a distinct type of infantile parkinsonism-dystonia that shares key clinical features with PD, including motor defici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 117 publications
(230 reference statements)
0
10
0
Order By: Relevance
“…These conformers occasionally gave rise to simultaneous opening of both the EC and IC gates such that formation of an intermittent water channel was detected. Notably, the sodium permeation pathway (Aguilar et al, 2021) coincides with that of water channeling (Cheng et al, 2018;Cheng and Bahar, 2019). This path, observed in silico, may also be associated with DATmediated ion fluxes or leak currents (Ingram et al, 2002;Erreger et al, 2008).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…These conformers occasionally gave rise to simultaneous opening of both the EC and IC gates such that formation of an intermittent water channel was detected. Notably, the sodium permeation pathway (Aguilar et al, 2021) coincides with that of water channeling (Cheng et al, 2018;Cheng and Bahar, 2019). This path, observed in silico, may also be associated with DATmediated ion fluxes or leak currents (Ingram et al, 2002;Erreger et al, 2008).…”
Section: Discussionmentioning
confidence: 64%
“…Recently, molecular modeling found that the infantile Parkinsonism-Dystonia associated substitution, R445C in hDAT, disrupted a phylogenetically conserved intracellular network of interactions and promoted a channel-like intermediate of hDAT. These rearrangements lead to the permeation of Na + from both the EC and IC solutions (Aguilar et al, 2021). Interestingly, docking simulations suggested that OCA could also bind near H444/R445 to stabilize the IF state or act as an anion-lipid (Figure 6A for OCA(−) in the IFo state).…”
Section: Discussionmentioning
confidence: 99%
“…It recently proved to have great translational potential in the case of folding-impaired DAT variants (Mazhar Asjad et al, 2017). We, and others, have examined the trafficking and activity of dopamine transporter deficiency syndrome (DTDS)-linked mutants in Drosophila ( Kasture et al, 2016 ; Mazhar Asjad et al, 2017; Aguilar et al, 2021 ). Drug screens carried out in Drosophila were led by data from in silico and in vitro experiments, and have also been validated in induced pluripotent stem cells (iPSCs) obtained from DTDS patients ( Ng et al, 2021 ).…”
Section: Animal Models In Exploring Slc6a1 Disorders: An Emphasis On ...mentioning
confidence: 99%
“…Experiments in cell culture show that many psychiatric disorder-associated DAT variants exhibit heterogenous molecular phenotypes, including differences in DA uptake kinetics, reverse transport, and altered binding to psychostimulant drugs [ 125 ]. Drosophila is an efficient model for studying the effects of human DAT mutants in vivo and have shown that DAT mutations associated with early-onset Parkinson’s [ 126 ] as well as ASD [ 107 ] lead to impairments in motor behavior. Drosophila is a feasible system for performing similar experiments to unravel the behavioral and molecular nature of DAT variants associated with ADHD, offering a practical model to identify the molecular mechanisms involved in response to psychostimulant drugs.…”
Section: Studying the Therapeutic Use Of Psychostimulants With Drosophilamentioning
confidence: 99%